Perception of teachers from regular education and special education on the new policies of inclusive education in Portugal - Magalhães, Joana (2010)
This article presents the result of a research project which its main objective was to explore the impact of the new inclusive education policies in the special education teachers’ and regular education teachers’ perceptions and attitudes. So, an exploratory study was conducted and four special education teachers and four regular education teachers were interviewed. The results of the research have highlighted that there is a positive attitude towards the legislation and inclusion, although they are many aspects that need to be improved, such as human and material resources.